Conjugation of the Consonantal Verb in the Ankawa Dialect - Andy Soulaka Slewa; Kawther Najeeb Askar (Zanco Journal of Human Sciences, 2026)
The Ankawa dialect is one of the Neo-Aramaic dialects in which the verb system has not previously been the subject of scholarly study. For this reason, the present research examines the Consonantal verb (biliteral, triliteral, and quadriliteral) in this dialect. The study adopts a descriptive–analytical methodology to achieve its objectives, whereby verbs were extracted from audio recordings conducted with native speakers of the dialect. The article analyzes the conjugations of five key forms, namely: the active participle, the perfect, the passive participle, the imperative, and the infinitive, within the three verbal patterns. (pʿal ܦܥܲܠ, paʿʿel ܦܲܥܸܠ,apʿel ܐܲܦܥܸܠ ) The research arrives at several conclusions, including, for example, the presence of all three patterns in this dialect, as well as the availability of examples representing each of the five conjugational forms. In addition to its academic and scientific value, the importance of this study lies in its documentation of the speech of elderly men and women who are native speakers of this endangered dialect.